Development of a test-bed for condition health monitoring of wind turbine gearbox - Yap, Calvin Jian Wei. (2010)
This report encompasses activities and tasks that were carried out by the author during his FYP on the development of a test-bed for condition health monitoring of a wind turbine gearbox, supervised by Assistant Professor Jaspreet Singh Dhupia. Prior to detailed report on the development phase of the test-bed, there will be an introduction to the motivation behind the project together with the project’s background and the objectives which the author aims to accomplish.